2017
DOI: 10.1007/s00228-017-2402-4
|View full text |Cite
|
Sign up to set email alerts
|

Drug use in pregnant women—a pilot study of the coherence between reported use of drugs and presence of drugs in plasma

Abstract: PurposeIn Sweden, information on drug use during pregnancy is obtained through an interview and recorded in a standardized medical record at every visit to the antenatal care clinic throughout the pregnancy. Antenatal, delivery, and neonatal records constitute the basis for the Swedish Medical Birth Register (MBR). The purpose of this exploratory study was to investigate the reliability of reported drug use by simultaneous screening for drug substances in the blood stream of the pregnant woman and thereby vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The pregnant women in our study seemed to be more inclined to use medication that was necessary or strongly recommended since only a small percentage refrained from accepting such treatment. This finding is supported by results from a study showing a good coherence between self‐reported medication intake noted in the antenatal records and the medication found in blood samples . Agreement between medication use noted in medical antenatal records and information from a national pharmacy database concerning medications used for chronic conditions was also high …”
Section: Discussionsupporting
confidence: 57%
“…The pregnant women in our study seemed to be more inclined to use medication that was necessary or strongly recommended since only a small percentage refrained from accepting such treatment. This finding is supported by results from a study showing a good coherence between self‐reported medication intake noted in the antenatal records and the medication found in blood samples . Agreement between medication use noted in medical antenatal records and information from a national pharmacy database concerning medications used for chronic conditions was also high …”
Section: Discussionsupporting
confidence: 57%
“…There are few studies that compare plasma drug levels to self-reported drug use, to investigate drug use in pregnancy. One Swedish study performed by Wolgast et al (2018) showed good concordance between reported drug use and drugs detected by LC-TOF-MS, in contrast to most studies which find a high incidence of under-reported drug use. In the Wolgast study, drugs that are only occasionally used, such as anti-histamines and analgesics; were detected at the highest frequency.…”
Section: Types Of Screening For Illicit Drugs In Pregnant Womenmentioning
confidence: 87%
“…2010 ), Norway ( Harris et al. 2017 ), and Sweden ( Wolgast et al. 2017 ) and a multi-national study (Europe, North/South America, and Australia) ( Lupattelli et al.…”
Section: Discussionmentioning
confidence: 99%